2021
DOI: 10.1080/24749508.2021.1952761
|View full text |Cite
|
Sign up to set email alerts
|

AHP based analysis of groundwater potential in the western escarpment of the Ethiopian rift valley

Abstract: This study investigated groundwater potential in the Western escarpment of the Ethiopian Rift valley, taking Dijo catchment as a case study, an area that is known for its critical shortage of water. Different thematic layers were used to determine the groundwater potential of the catchment. PCI Geomatica and Rockwork were used to automatically extract lineament and lineament orientation, respectively. Weights of parameters were computed using the analytical hierarchy process (AHP). Rank was assigned to each fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…There are studies done to assess and evaluate the water resources in the CRV and the Rift Valley. Among these studies are: Comparative assessment of the water balance and hydrology of selected Ethiopian and Kenyan Rift Lakes (Ayenew and Becht, 2008) (Thomas et al, 2019); Analytical Hierarchal Process (AHP) based analysis of groundwater potential in the western escarpment of the Ethiopian rift valley (Abrar et al, 2021); Groundwater Resources in the Main Ethiopian Rift Valley: An Overview for a Sustainable Development (Bonetto et al, 2021); and Quantifying the Regional Water Balance of the Ethiopian Rift Valley Lake Basin Using an Uncertainty Estimation Framework (Abraham et al, 2021). However, there are significant differences in the figures they are providing, and in the approaches, they are following.…”
Section: Groundwater and Related Research In The Crv And Their Connec...mentioning
confidence: 99%
“…There are studies done to assess and evaluate the water resources in the CRV and the Rift Valley. Among these studies are: Comparative assessment of the water balance and hydrology of selected Ethiopian and Kenyan Rift Lakes (Ayenew and Becht, 2008) (Thomas et al, 2019); Analytical Hierarchal Process (AHP) based analysis of groundwater potential in the western escarpment of the Ethiopian rift valley (Abrar et al, 2021); Groundwater Resources in the Main Ethiopian Rift Valley: An Overview for a Sustainable Development (Bonetto et al, 2021); and Quantifying the Regional Water Balance of the Ethiopian Rift Valley Lake Basin Using an Uncertainty Estimation Framework (Abraham et al, 2021). However, there are significant differences in the figures they are providing, and in the approaches, they are following.…”
Section: Groundwater and Related Research In The Crv And Their Connec...mentioning
confidence: 99%
“…The accuracy of the potential map depends on how precisely the weights are assigned to each layer [19]. Researchers used several methods in assigning accurate weights to the thematic layers and the AHP method is widely used [13,15,22,65,66]. In this study, groundwater potential zones were identified using AHP-aided methodology.…”
Section: Groundwater Potential Zonesmentioning
confidence: 99%
“…The rapid growth of space technology has played a vital role in groundwater studies. Remote sensing (Rs) and the geographic information system (GIS) are promising tools for the efficient planning and management of groundwater resources [19][20][21][22]. NRSA, in India, is one of the pioneers in using the integrated study of RS and GIS for delineating groundwater recharge potential in an area [23].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-criteria decision analysis via analytical hierarchy process is the most popular and well known GIS based approach used for land and water management (Saaty, 1980;Arulbalaji et al, 2019;Abijith et al, 2020;Rajesh et al, 2021, Abrar et al, 2021, Doke et al, 2021. AHP helps in integrating all thematic layers (Saranya and Saravanan, 2020).…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
“…Water flows downward from higher to lower elevations. Lower elevated area were assigned a higher weight while highly elevated areas were assigned a lower weight (Abrar et al, 2021). Studies from the previous year have shown that water potential zones increase with lower topographic elevations (Awawdeh et al, 2014).…”
Section: Elevationmentioning
confidence: 99%